PENGARUH INTELLECTUAL CAPITAL, BUSINESS RISK, CORPORATE GOVERNANCE, PER, DEBT POLICY, ROA, DAN DAR TERHADAP FIRM VALUE - Ahmad Irmizi; Magda Siahaan (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to obtain empirical evidence regarding whether intellectual capital, business risk, managerial ownership, institutional ownership, price earning ratios, debt policy, return on assets, and debt to asset ratio have an influence on firm value. This research data consists of 50 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for three years, namely in the research period from 2017 to 2019.The sample chosen is by using purposive sampling method. Methods of data analysis in this study using a hypothesis method with multiple linear regression. The results showed that the variable price earning ratio and return on assets had a positive effect and the business risk variable had a negative effect on the firm value variable. Meanwhile, the other five variables, namely intellectual capital, managerial ownership, institutional ownership, debt policy, and debt to asset ratio, have no effect on firm value.